Synergistic effects of fluorinated substituents and Fe(Ⅱ) on ferrihydrite transformation and antibiotic degradation - Liting Wang; Shikun Wei; Liwen Zhang; Zhiyong Guo; Yan Lei; Deming Dong (Ecotoxicology and Environmental Safety)
Ferrihydrite is commonly associated with antibiotics in natural environments due to its strong sorption capabilities and high specific surface area. Under reducing conditions, Fe(II) acts as a catalyst for the transformation of ferrihydrite into more crystalline minerals. However, the influence of antibiotic molecular structure on the Fe(II)-catalyzed transformation of ferrihydrite and the associated degradation mechanisms of antibiotics have remained unclear. This study employed enoxacin (ENO), a representative fluorinated pharmaceutical, and pipemidic acid (PPA), a structural analog of ENO, to investigate the effect of fluorinated substituents on Fe(II)-facilitated ferrihydrite transformation. The results revealed that the transformation of ferrihydrite in the ENO system was 2.8 times greater than in the PPA system. ENO degradation reached 74.3 %, which was 1.13 times higher than that of PPA. ENO degradation products were more prone to hydroxylation, decarboxylation, and piperazine ring oxidation, whereas PPA degradation primarily involved oxidation of the piperazine ring. The fluorinated substituent in ENO facilitated ferrihydrite transformation by influencing the concentration of adsorbed Fe(II) and the distribution of antibiotics within the mineral inside. Furthermore, the fluorinated substituent in ENO enhanced degradation by increasing electron transfer between ENO and Fe(III), raising the content of adsorbed Fe(II) and promoting the formation of goethite. Collectively, these findings provide new insights into the environmental behavior of ferrihydrite and the fate of structurally different antibiotics in natural systems.